The impact of ownership characteristics and gender on earnings management: Indonesian c1-1ompanies - Ari Kuncara Widagdo; Rahmawati; Djuminah; Siti Arifah; Francisca Sestri Goestjahjanti; Kiswanto (Journal of Risk and Financial Management, 2023)
Earnings management is a behavior performed by management to show good performance to principals. This effort creates information bias in the study of agency theory, which in turn increases information asymmetry. In Indonesia, the average company has a family ownership structure. Therefore, this study aims to examine the effect of family ownership characteristics and gender on earnings management. This study includes gender diversity in the board of commissioners and board of directors. This research uses the non-financial companies' data in Indonesian Capital Market. Furthermore, the data were analyzed using multiple regression based on ordinary least squares. Research results show that the proportion of females in both board of commissioners and board of directors, as well as company size contribute significantly to earnings management, whereas, family ownership, ROA, and leverage do not have a significant impact. This research provides a practical contribution to the study of the composition of the board of commissioners and directors regarding earnings management actions for owners, investors and other stakeholders.
Keywords: 650; earnings management; gender; family ownership